Pola Aktivitas Wisatawan di Daya Tarik Wisata Aek Milas dan Legenda Sampuraga Kabupaten Mandailing Natal - Andry Paisal; Trisna Putra (Departemen Pariwisata Universitas Negeri Padang, 2022)
Aek Milas and the Legend of Sampuraga are one of the leading tourist attractions in Mandailing Natal Regency, North Sumatra, the area of ​​​​this tourist area is approximately 2 hectares, this area is always crowded with visitors on holidays but the presence of visitors in the area is not regular, the accumulation of visitors at one point, and does not yet have a pattern of activity in the area. Setting the pattern of tourist activity in the area is very important so that the tourism potential can be more optimally managed properly, for that it is necessary to design a pattern of tourist activity in that location. From observations and interviews conducted with related parties, it was found that a pattern that made it possible for the friend was suitable, namely the Chaining Loop model. The Chaining Loop pattern is adopted from the tourist travel pattern with the addition of facilities and infrastructure through the 6A concept (Attraction, Amenities, Ancillary, Activities, Accessibilities, Accommodation) that can attract tourists' attention.